How We Write: Thirteen Ways of Looking at a Blank Page - Akbari, Suzanne Conklin; Project Muse; Project Muse. (Project Muse, 2020)
This little book arose spontaneously, in the late spring of 2015, when a series of conversations emerged -- first in a university roundtable on graduate student dissertation-writing, and then in a rapidly proliferating series of blog posts -- on the topic of how we write. One commentary generated another, each one characterized by enormous speed, eloquence, and emotional forthrightness. This collection is not about how TO write, but how WE write: unlike a prescriptive manual that promises to unlock the secret to efficient productivity, the contributors talk about their own writing processes, in all their messy, frustrated, exuberant, and awkward dis/order. The contributors range from graduate students and recent PhDs to senior scholars working in the fields of medieval studies, art history, English literature, poetics, early modern studies, musicology, and geography. All are engaged in academic writing, but some of the contributors also publish in other genres, includes poetry and fiction. Several contributors maintain a very active online presence, including blogs and websites; all are committed to strengthening the bonds of community, both in person and online, which helps to explain the effervescent sense of collegiality that pervades the volume, creating linkages across essays and extending outward into the wide world of writers and readers.
Introduction: written chatter and the writer's voice / Suzanne Conklin Akbari -- About the images -- Who we are -- Wilderness group tour / Michael Collins -- How I write (1) / Suzanne Conklin Akbari -- How I write (2) / Alexandra Gillespie -- The community you have, the community you need: on accountability groups / Alice Hutton Sharp -- This would be better if I had a co-author / Asa Simon Mittman -- On the necessity of ignoring those who offer themselves as examples / Jeffrey Jerome Cohen -- How I write (3) / Maura Nolan -- Errant practices / Richard H. Godden -- Cushion, kernel, craft / Bruce Holsinger -- Writing by accumulation / Stuart Elden -- Travelling through words / Derek Gregory -- Wet work: writing as encounter / Steven Mentz -- Writing (life): ten lessons / Daniel T. Kline.
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Academic writing; Authorship; Electronic books; Electronic books